URGENSI KUALITAS PELAYANAN PERPUSTAKAAN PERGURUAN TINGGI - Rodin, Rhoni (Jurnal Kajian Informasi dan Perpustakaan, 2015)
The quality of the library service refers to the needs of users. Therefore, a good service is a service that can meet the needs and wishes of the user. Then a good library is a library which is able to provide services to every pemustaka quickly and accurately. Now the theory that is used in this study among others: service quality, the dimension of the quality of service, the determining factors in the quality of service and supervision. The discussion is a total quality services can be influenced by several factors among others: word of "communication, personal need, good past experience, external communications to customer. The conclusion is that there are several factors that can improve the quality of the service on an institution that is the purpose of the organization, incentive system that used the system accountability and power structures. As an institution that performs the activity of the ministry and the library has an obligation to continually improve the quality of the service in order to meet the needs of users.Kualitas layanan perpustakaan mengacu kepada kebutuhan pemustaka. Oleh sebab itu, layanan yang baik adalah layanan yang dapat memenuhi kebutuhan dan harapan pemustaka. Maka perpustakaan yang baik merupakan perpustakaan yang dapat memberikan pelayanan kepada setiap pemustaka secara cepat dan tepat. Adapun teori yang digunakan dalam kajian ini antara lain: Kualitas pelayanan, dimensi kualitas pelayanan, faktor penentu kualitas pelayanan dan pengawasan. Pembahasannya adalah Kualitas total suatu jasa dapat dipengaruhi oleh beberapa faktor antara lain: word of mouth communication, personal need, past experience, external communications to customer. Kesimpulannya adalah Ada beberapa faktor yang dapat meningkatkan kualitas layanan pada sebuah lembaga yaitu tujuan  organisasi,  sistem  insentif  yang dipakai, sistem akuntabilitas dan struktur kekuasaan. Sebagai   sebuah   lembaga   yang   melakukan aktifitas pelayanan, maka perpustakaan berkewajiban untuk senantiasa meningkatkan kualitas layanannya, agar dapat memenuhi kebutuhan dari para pemustaka.